2015
DOI: 10.1002/ccd.25909
|View full text |Cite
|
Sign up to set email alerts
|

Cost implications of intraprocedural thrombotic events during PCI

Abstract: The occurrence of IPTE during the index PCI in patients with NSTEACS is associated with substantial increases in-hospital and 30-day costs. These findings suggest that strategies to prevent IPTE may be associated with important cost offsets as well as improved clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…As has been shown in in previous work, these complications are associated with serious adverse outcomes in follow‐up Conversely, we also find that over 60% of thrombotic catheterization laboratory events do not result in a post‐PCI complication, but these events nevertheless significantly increase costs and thus should be considered in economic analyses. Precise data quantifying the economic impact of these complications are scarce Our study leverages the advantages of a large multi‐center, contemporary study to provide estimates of the economic burden of thrombotic events for PCI patients with broader spectrum of syndromes including stable angina and ACS.…”
Section: Discussionmentioning
confidence: 99%
“…As has been shown in in previous work, these complications are associated with serious adverse outcomes in follow‐up Conversely, we also find that over 60% of thrombotic catheterization laboratory events do not result in a post‐PCI complication, but these events nevertheless significantly increase costs and thus should be considered in economic analyses. Precise data quantifying the economic impact of these complications are scarce Our study leverages the advantages of a large multi‐center, contemporary study to provide estimates of the economic burden of thrombotic events for PCI patients with broader spectrum of syndromes including stable angina and ACS.…”
Section: Discussionmentioning
confidence: 99%
“…A subanalysis of the ACUITY trial showed that patients with non-STsegment elevation ACS undergoing PCI who experienced IPTE had a higher median rate of in-hospital and 30-day costs compared with those without IPTE ($23,719 vs $18,419, and $23,719 vs $19,556, respectively; p = 0.01 and p = 0.05, respectively). Overall, the occurrence of IPTE in patients with non-ST-segment elevation ACS was associated with substantial increases in in-hospital and 30-day costs [25].…”
Section: Other Percutaneous Coronary Intervention-related Complicationsmentioning
confidence: 99%
“…The occurrence of intraprocedural thrombotic events (IPTE), including periprocedural MI, stent thrombosis, new or increasing thrombus, abrupt vessel closure, no or slow reflow, and distal embolization, have been demonstrated to be independent predictors of both early and late adverse clinical outcomes in patients undergoing PCI [24,25]. These acute ischemic complications are associated with approximately 20% increases in inhospital and 30-day costs [19,25].…”
Section: Other Percutaneous Coronary Intervention-related Complicationsmentioning
confidence: 99%
“…In this current issue of the journal, Plent et al assessed the impact of IPTE on in‐hospital and 30‐day cost in a 1,307 patient subgroup from the ACUITY trial with NSTEACS who underwent PCI . Similar to the previously published incidence of 3.5%, 52 patients (4.0%) developed IPTE during the index PCI.…”
mentioning
confidence: 95%
“…But not all IPTE are created equal (or cost the same). Patients that experienced intraprocedural stent thrombosis, acute vessel closure, or developed new/progressive thrombus had a much higher cost compared with side branch closure or slow reflow . The importance of baseline thrombus was again highlighted, with 48.1% of patients with IPTE having baseline thrombolysis in myocardial infarctions (TIMI) flow 0/1 while only 12.7% of patients without IPTE had TIMI flow 0/1.…”
mentioning
confidence: 99%